Evaluation of insecticidal schedules for the management of insect pests of potato (The Journal of Plant Protection Sciences, 2020)
Two year's field study was undertaken to evaluate the efficacy of five treatments against insect pests of potato. The minimum population of aphids, whitefly and epilachna beetle was observed in the treatment T1 which received soil application of phorate followed by spraying of chlorpyriphos, imadicloprid and cartap hydrochloride, respectively at 40, 55 and 70 DAP than other treatments. Maximum yield of healty potato tuber was recorded in the plot treated with chlorpyriphos before planting and foliar spray of acephate, imadichloprid and chlorpyriphos + cypermethrin at 40, 55 and 70 DAP (T2). Yield of damaged tuber caused by soil pests was found maximum in control plot and it was recorded lowest in T4 treatment which received soil application of phorate 10G at 40 DAP and foliar spray with imadichloprid and chlorpyriphos + cypermethrin at 55 and 70 DAP, respectively. But soil application of phorate at planting followed by spraying of chlorpyriphos, azadirachtin and Bt (T3) was not as effective as T4.
Keywords: Insect pests; insecticides; pest complex; potato